Challenging the Master: Lessons from Rethinking The Crit (EAAE Annual Conference Proceedings, 2023)
Alberti’s 1485 book On The Art of Building describes the design process as one where the architect applies absolute authority and claims ownership and credit through developing judgement. These necessary judgement skills are developed in the crit setting by the public presentation of work; the student both experiences judgement (of their own work) and observes the judgement (of their peer’s work).